Critical International Political Economy - Shields, Stuart. author. aut Link
XIII, 195 p.
Keywords: Amidst the continued debate surrounding the foundations of IPE and recent methodological and theoretical divides, the authors argue that an attempt should be made to re-visit the notion of the 'critical'. They assess the development of so-called critical IPE and interrogate whether the theoretical foundations it was built upon have reached their potential. This challenge is taken up in a number of different ways, but all share a common concern: to re-assess the purpose of critical approaches and to reflect on why certain social theorists have been favoured as a point of departure, yet others have largely been ignored. In light of recent debates on the notion of a 'trans-Atlantic divide' within IPE, this book demonstrates how the distinction between the 'critical' and the 'orthodox' (or 'empirical') is only significant if the 'critical' is geared towards a larger, more substantial body of critical social enquiry and engages with what it means to conduct such enquiry.